Laminate manufacturing method and compact manufacturing method

The method of forming a primer layer with an acrylic resin on a paper base material and then applying a poly(hydroxyalkanoate) resin layer addresses the issues of insufficient water and oil resistance, pinholes, and curling in existing laminate manufacturing processes, resulting in a laminate with improved performance for packaging materials.

JP2025070388APending Publication Date: 2025-05-02KANEKA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023180668
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing methods for manufacturing laminates with a poly(hydroxyalkanoate) resin layer on a paper base material result in insufficient water and oil resistance, pinholes, and curling issues, making them unsuitable for packaging materials, especially those with high oil content.

Method used

A method involving the formation of a primer layer containing an acrylic resin on the paper base material, followed by the application of a poly(hydroxyalkanoate) resin layer, which is then heated to a specific temperature range to form a resin layer with improved uniformity and adhesion.

Benefits of technology

The proposed method achieves a laminate with enhanced oil resistance, reduced pinholes, minimal curling, and improved adhesion between the paper base and the resin layer, making it suitable for packaging materials with high oil content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025070388000001
    Figure 2025070388000001
Patent Text Reader

Abstract

To provide a laminate manufacturing method which enables application of a laminate including a paper base material and a resin layer containing a poly (hydroxy alkanoate)-based resin to a packaging material of a foodstuff limited in curling, having limited pinholes on the surface of the resin layer, exhibiting excellent oil resistance, and containing much oil.SOLUTION: This manufacturing method comprises: a step [step (i)] of coating the surface of a paper base material with an aqueous coating liquid containing an acrylic resin, and then heating the surface to form a primer layer (B); and a step [step (ii)] of coating the surface of the primer layer (B) with an aqueous dispersion liquid containing a poly (hydroxy alkanoate)-based resin to form a coating film, and heating the surface so that the surface temperature of the coating film can become a melting point (Tm)+5°C-Tm+20°C of the poly (hydroxy alkanoate)-based resin to form a resin layer (C).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a laminate having a resin layer containing a poly(hydroxyalkanoate) resin, and a method for producing a molded article containing the laminate. [Background technology]

[0002] In recent years, environmental issues caused by discarded plastics have been attracting attention. In particular, marine pollution caused by discarded plastics is serious, and there are hopes for the widespread use of biodegradable plastics that decompose in the natural environment.

[0003] Various types of such biodegradable plastics are known, but one particular example is poly(3-hydroxybutyrate) resin, a type of poly(hydroxyalkanoate) resin (hereinafter also referred to as PHA). This is a thermoplastic polyester that is produced and accumulated as an energy storage substance within the cells of many microbial species, and is a material that can biodegrade not only in soil but also in seawater, and is therefore attracting attention as a material that can solve the above problems.

[0004] A laminate obtained by laminating a layer mainly composed of a poly(hydroxyalkanoate)-based resin, such as a poly(3-hydroxybutyrate)-based resin, onto a biodegradable paper substrate is extremely promising from the standpoint of environmental protection, since both the resin and the substrate are materials with excellent biodegradability.

[0005] As an example of a method for producing such a laminate, Patent Document 1 describes a method in which an aqueous dispersion containing a copolymer of 3-hydroxybutyrate and 3-hydroxyhexanoate having a specific average molecular weight is applied to a substrate, and then the substrate is heated and dried to form a film. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2021 / 075412 Summary of the Invention [Problem to be solved by the invention]

[0007] According to the manufacturing method described in Patent Document 1, in which an aqueous dispersion of a resin is applied to a paper substrate, and then heated to dry and form a film, it is possible to produce a laminate in which a resin layer mainly composed of a poly(hydroxyalkanoate)-based resin is laminated on a paper substrate. However, when the surface of the resin layer of the laminate obtained by the manufacturing method described in Patent Document 1 was observed with an electron microscope, it was found that the interface between the resin particles remained, and the water resistance and oil resistance were insufficient. By setting the temperature during heating and drying high, it was possible to melt the particles and improve the uniformity of the resin layer, but the pinholes did not disappear completely, and the oil resistance was still insufficient for application as a packaging material for foods that contain a lot of oil. In addition, the laminate curls (curves) when heated at high temperatures, which can cause transportation problems when forming it into bags or containers, leaving room for improvement.

[0008] In view of the above-mentioned current situation, the present invention aims to provide a method for producing a laminate having a paper base material and a resin layer containing a poly(hydroxyalkanoate) resin, which has little curl, few pinholes on the surface of the resin layer, excellent oil resistance, and can be used as a packaging material for foods that contain a lot of oil. [Means for solving the problem]

[0009] As a result of intensive research into solving the above-mentioned problems, the inventors discovered that in a method for manufacturing a laminate having a paper base material and a resin layer containing a poly(hydroxyalkanoate) resin, the above-mentioned problems can be solved by forming a primer layer containing an acrylic resin on the surface of the paper base material and then forming a resin layer on the surface of the primer layer, and thus completed the present invention.

[0010] That is, the present invention relates to a method for producing a laminate having a paper base material (A) and, on at least one side of the paper base material (A), a primer layer (B) and a resin layer (C) containing a poly(hydroxyalkanoate)-based resin, the method comprising sequentially carrying out at least the following steps (i) and (ii): Process (i); A step of applying an aqueous coating liquid containing an acrylic resin to the surface of the paper base material and heating the applied liquid to form a primer layer (B). Step (ii); A process of forming a coating film by applying an aqueous dispersion containing a poly(3-hydroxyalkanoate) resin to the surface of the primer layer (B) obtained in the process (i), and heating the coating film so that the surface temperature is within the melting point (Tm) of the poly(hydroxyalkanoate) resin + 5°C to Tm + 20°C to form a resin layer (C). Effect of the Invention

[0011] According to the present invention, a method for producing a laminate having a paper base material and a resin layer containing a poly(hydroxyalkanoate)-based resin can be provided, which has few pinholes on the surface of the resin layer and has excellent oil resistance, and can be used as a packaging material for foods that contain a lot of oil.

[0012] Furthermore, the present invention makes it possible to produce a laminate that has little curl, excellent adhesion strength between the paper base material and the resin layer, and excellent formability when secondary processed into packaging materials such as bags, lids, and containers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.

[0014] [Laminate] A laminate according to an embodiment of the present disclosure has a primer layer (B) and a resin layer (C) containing a poly(hydroxyalkanoate) resin on at least one side of a paper substrate (A), and the resin layer (C) is laminated via the primer layer (B). The primer layer (B) may be laminated directly on the paper substrate (A), or may further include another layer between the primer layer (B) and the paper substrate (A) as long as the adhesion of the primer layer (B) to the paper substrate (A) and the uniformity during layer formation are not impaired. In a preferred embodiment, the laminate as a whole is biodegradable.

[0015] In one embodiment of the present disclosure, the resin layer (C) may be the outermost layer in the laminate. In this case, the resin layer (C) may function as a water-resistant layer, an oil-resistant layer, and / or a heat seal layer.

[0016] In another embodiment of the present disclosure, another layer may be laminated on the resin layer (C) for the purpose of imparting water resistance, oil resistance, design, or adhesiveness. In this case, the resin layer (C) may function as an anchor coat layer between the paper substrate (A) and the other layer. The other layer is not particularly limited and may be another resin layer or an inorganic layer, and an example thereof is the second resin layer described later.

[0017] The surface of the paper base material (A) opposite to the side on which the resin layer (C) is laminated may be the outermost layer, or may have some other layer laminated thereon. The layer may be a layer consisting of the primer layer (B) and the resin layer (C), or may be a printed layer or the like. The resin layer (C) may be formed without the primer layer (B) depending on the required function.

[0018] (Paper base material) Paper is composed of a sheet mainly made of pulp. The paper base material can be obtained by papermaking a stock containing pulp, a filler, various auxiliaries, etc. The type of paper that can be used is not particularly limited, and examples include cup base paper, kraft paper, fine paper, coated paper, tissue paper, glassine paper, paperboard, and the like.

[0019] The pulp is not particularly limited, and examples thereof include chemical pulps such as bleached hardwood kraft pulp (LBKP), bleached softwood kraft pulp (NBKP), unbleached hardwood kraft pulp (LUKP), unbleached softwood pulp (NUKP), and sulfite pulp; mechanical pulps such as stone-ground pulp and thermomechanical pulp; wood fibers such as deinked pulp and waste paper pulp; and non-wood fibers obtained from kenaf, bamboo, hemp, etc. These can be used in appropriate combination.

[0020] Among these, it is preferable to use chemical pulp or mechanical pulp made from wood fibers, and it is more preferable to use chemical pulp, because the paper is less likely to be contaminated with foreign matter, is less likely to discolor over time when recycled as a waste paper raw material, has a high whiteness level, which results in a good surface appearance when printed, and is particularly valuable when used as a packaging material. Specifically, the amount of chemical pulp such as LBKP or NBKP in the pulp is preferably 80% or more, and it is particularly preferable that the amount of chemical pulp is 100%.

[0021] The filler is not particularly limited, and examples thereof include inorganic fillers such as talc, kaolin, calcined kaolin, clay, heavy calcium carbonate, light calcium carbonate, white carbon, zeolite, magnesium carbonate, barium carbonate, titanium dioxide, zinc oxide, silicon oxide, amorphous silica, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, zinc hydroxide, barium sulfate, and calcium sulfate; and organic fillers such as urea-formalin resin, polystyrene resin, phenolic resin, and hollow microparticles. Note that the filler is not an essential material and may not be used.

[0022] The various auxiliaries are not particularly limited, and examples thereof include sizing agents such as rosin, alkyl ketene dimer (AKD), and alkenyl succinic anhydride (ASA), polyacrylamide polymers, polyvinyl alcohol polymers, cationic starch, various modified starches, dry strength agents such as urea-formaldehyde resin and melamine-formaldehyde resin, wet strength agents, retention agents, drainage improvers, coagulants, aluminum sulfate, bulking agents, dyes, fluorescent whitening agents, pH adjusters, defoamers, ultraviolet inhibitors, anti-fading agents, pitch control agents, slime control agents, etc. These may be appropriately selected and used as needed.

[0023] The paper forming the paper base material may have its surface treated with various chemicals. The chemicals are not particularly limited, and examples thereof include oxidized starch, hydroxyethyl etherified starch, enzyme-modified starch, polyacrylamide, polyvinyl alcohol, surface sizing agents, water-resistant agents, water retention agents, thickeners, lubricants, etc. Only one type of chemical may be used, or two or more types may be used in combination. Furthermore, these chemicals may be used in combination with pigments.

[0024] The pigment is not particularly limited, and examples thereof include inorganic pigments such as kaolin, clay, engineered kaolin, delaminated clay, heavy calcium carbonate, light calcium carbonate, mica, talc, titanium dioxide, barium sulfate, calcium sulfate, zinc oxide, silicic acid, silicate salts, colloidal silica, and satin white; and organic pigments such as solid, hollow, and core-shell types. Only one type of pigment may be used, or two or more types may be used in combination.

[0025] The basis weight of the paper base material can be appropriately selected depending on the desired quality and the application of the laminate, but is preferably 40 g / m 2 More than 400g / m 2 It is preferable that the thickness is less than 50 g / m 2 More than 350g / m 2 When the laminate is used for packaging materials such as wrapping paper, paper bags, lids, lining papers, and soft packaging materials, and for posters to be used outdoors, the preferred thickness is 40 g / m 2 More than 150g / m 2It is more preferable that the soft packaging material is a packaging material having a density of 40 g / m or less. 2 ~100g / m 2 It refers to a flexible packaging material using thin paper of about 150 g / m2. In addition, when the laminate is used for paper tableware such as paper cups, paper boxes, paper plates, paper trays, etc., or for lids and other paper containers, the thickness is set at 150 g / m2. 2 More than 400g / m 2 It is even more preferable that:

[0026] The density of the paper base material can be appropriately selected depending on the desired quality, handling properties, etc., but is usually 0.5 g / cm 3 More than 1.0g / cm 3 It is preferable that:

[0027] The method of manufacturing the paper base material (papermaking) is not particularly limited, and can be carried out by appropriately selecting a known papermaking machine such as a Fourdrinier papermaking machine, a cylinder papermaking machine, a short wire papermaking machine, a twin wire papermaking machine such as a gap former type or a hybrid former type (on-top former type). The pH during papermaking may be in the acidic range (acidic papermaking), pseudo-neutral range (pseudo-neutral papermaking), neutral range (neutral papermaking), or alkaline range (alkaline papermaking), and after papermaking in the acidic range, an alkaline agent may be applied to the surface of the paper layer. The paper base material may be one layer, or may be composed of two or more layers.

[0028] When treating the surface of a paper substrate with a chemical, the method of surface treatment is not particularly limited, and known coating devices such as a rod metering size press, a pond type size press, a gate roll coater, a spray coater, a blade coater, or a curtain coater can be used. (Primer layer) The primer layer has the effect of filling and smoothing the unevenness of the pulp of the paper substrate, thereby improving the wettability to the paper substrate when the poly(hydroxyalkanoate) resin is melted by heating to form a resin layer, and suppressing the occurrence of pinholes. Therefore, as described above, it is preferable that the laminate of the present invention has a primer layer between the paper substrate and the resin layer, and the resin layer and the primer layer are directly laminated. In particular, since the affinity with poly(hydroxyalkanoate)-based resins is excellent, it is preferable that the primer layer contains an acrylic resin as an essential component. Examples of monomers constituting the acrylic resin include unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, cinnamic acid, itaconic acid, fumaric acid, maleic acid, and butene tricarboxylic acid, alkyl methacrylates such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, benzyl acrylate, 2-hydroxyethyl acrylate, glycidyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, butyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, 2-ethylhexyl methacrylate, lauryl methacrylate, stearyl methacrylate, and cyclohexyl methacrylate. Examples of the monomer include unsaturated carboxylic acid esters having at least one carboxyl group, such as ester, phenyl methacrylate, benzyl methacrylate, isobornyl methacrylate, glycidyl methacrylate, tetrahydrofurfuryl methacrylate, allyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-methoxyethyl methacrylate, 2-ethoxyethyl methacrylate, monoethyl itaconic acid ester, monobutyl fumarate ester, and monobutyl maleate ester, and unsaturated sulfonic acid compounds or salts thereof, such as acrylamidopropanesulfonic acid, sodium sulfoethyl acrylate, and sodium sulfopropyl methacrylate. In addition, other monomers copolymerizable with these monomers may be used in combination, and examples of such monomers include aromatic vinyl compounds such as styrene, α-methylstyrene, vinyltoluene, pt-butylstyrene, and chlorostyrene. These monomers are not particularly limited, and only one type may be used, or two or more types may be used in combination as necessary. The acrylic resin is preferably dispersed (including emulsified) or dissolved in an aqueous solvent in the form used for producing the laminate, since the acrylic resin can be heated, dried, and formed into a film on the paper substrate to obtain a paper substrate sealing effect with a small coating weight. In particular, the acrylic resin is more preferably an aqueous emulsion, since it is obtained by emulsion polymerization of the above-mentioned monomer mixture together with water and an emulsifier, and is easily available industrially. The aqueous solvent may contain alcohols such as isopropyl alcohol, ketones such as methyl ethyl ketone, etc., in order to improve the wettability and drying property of the paper substrate. Commercially available aqueous emulsions of acrylic resins include, for example, "Ultrasol (registered trademark)" from AICA Kogyo Co., Ltd., "JONCRYL (registered trademark)" from BASF Ltd., "FILLHARMO (registered trademark)" from TOYOCHEM CO., LTD., and "SEIKOAT (registered trademark)" from SEIKO PMC CORPORATION. The glass transition temperature of the acrylic resin is preferably −30° C. or higher and 90° C. or lower, more preferably −20° C. or higher and 50° C. or lower, and particularly preferably −15° C. or higher and 30° C. or lower. By setting the glass transition temperature at this temperature, the aqueous emulsion can be made into a film at a low temperature when it is coated, dried and formed into a film, and a high filling effect of the paper base material can be obtained while avoiding a decrease in mechanical strength due to a decrease in the moisture content of the paper base material. The primer layer (B) may contain only one type of the acrylic resin, or may contain a mixture of two or more types of the acrylic resin. The primer layer (B) may contain a resin component other than the acrylic resin within a range that does not impair the effects of the present invention. Examples of the resin component other than the acrylic resin include polyamide resin, polyethyleneimine, polyvinylamine, styrene-butadiene resin, vinyl chloride resin, olefin-unsaturated carboxylic acid resin, modified polyolefin, ionomer resin, vinyl acetate resin, urethane resin, polyvinyl alcohol, modified polyvinyl alcohol, starch and its derivatives, cellulose derivatives, polyvinylpyrrolidone, polyester resin, etc., and these resins can be used alone or in combination of two or more kinds. The content of these resin components is preferably 20% by weight or less, more preferably 10% by weight or less, and particularly preferably 5% by weight or less, of the total amount of the primer layer. The polyester-based resin contained in the primer layer is not particularly limited, but is preferably a biodegradable polyester-based resin, and examples of the polyester-based resin include aliphatic polyester-based resins such as poly(hydroxyalkanoate), polylactic acid, polybutylene succinate, and polybutylene succinate adipate, and aliphatic aromatic polyester-based resins such as polybutylene adipate terephthalate, polybutylene sebate terephthalate, polybutylene azelate terephthalate, and polycaprolactone. In addition to the above-mentioned resin components, the primer layer may contain additives such as fillers, pigments, lubricants, dispersants, surfactants, antifoaming agents, dyes, thickeners, etc., as necessary. The method for mixing these components is not particularly limited, but for example, they may be added directly to an aqueous emulsion containing an acrylic resin, or may be prepared separately by dispersing (including emulsifying) or dissolving in an aqueous solvent and then mixed. Of the biodegradable polyester resins, polyhydroxyalkanoate, polylactic acid, polybutylene succinate, and polybutylene succinate adipate can also be mixed using commercially available products dispersed (including emulsified) in an aqueous solvent. (Resin layer) The resin layer formed on at least one surface of the paper substrate contains at least a poly(hydroxyalkanoate) resin. Only one type of PHA may be used, or two or more types may be used in combination. The resin component contained in the resin layer may be only PHA, or may further contain another resin. The other resin may be a biodegradable resin described later.

[0029] The poly(hydroxyalkanoate) resin is a general term for polymers that have hydroxyalkanoic acid as a monomer unit. The hydroxyalkanoic acid that constitutes PHA is not particularly limited, but examples thereof include 3-hydroxybutanoic acid, 4-hydroxybutanoic acid, 3-hydroxypropionic acid, 3-hydroxypentanoic acid, 3-hydroxyhexanoic acid, 3-hydroxyheptanoic acid, and 3-hydroxyoctanoic acid. PHA may be a homopolymer or a copolymer containing two or more kinds of monomer units.

[0030] The resin layer preferably contains PHA in an amount of 50% by weight or more, more preferably 70% by weight or more, even more preferably 80% by weight or more, and even more preferably 90% by weight or more. By using PHA as a main component, the resin layer can exhibit biodegradability.

[0031] The PHA is preferably a poly(3-hydroxybutyrate) resin (hereinafter also referred to as P3HB). P3HB refers to a homopolymer having only 3-hydroxybutyrate units and / or a copolymer containing 3-hydroxybutyrate units and other hydroxyalkanoate units. From the viewpoint of seawater decomposition, it is preferable to include a copolymer containing 3-hydroxybutyrate units and other hydroxyalkanoate units.

[0032] The type of copolymerization in the copolymer is not particularly limited, and may be random copolymerization, alternating copolymerization, block copolymerization, graft copolymerization, etc. Copolymers produced by microorganisms are usually random copolymers.

[0033] The hydroxyalkanoic acid forming the other hydroxyalkanoate unit is not particularly limited, and examples thereof include 4-hydroxybutanoic acid, 3-hydroxypropionic acid, 3-hydroxypentanoic acid, 3-hydroxyhexanoic acid, 3-hydroxyheptanoic acid, and 3-hydroxyoctanoic acid. In terms of excellent balance of properties, 4-hydroxybutanoic acid and 3-hydroxyhexanoic acid are particularly preferred.

[0034] Specific examples of P3HB include poly(3-hydroxybutyrate) (abbreviation: PHB), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (abbreviation: P3HB3HH), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (abbreviation: P3HB3HV), poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (abbreviation: P3HB4HB), and poly(3-hydroxybutyrate-co-3 -hydroxyoctanoate) (abbreviation: P3HB3HO), poly(3-hydroxybutyrate-co-3-hydroxyoctadecanoate) (abbreviation: P3HB3HOD), poly(3-hydroxybutyrate-co-3-hydroxydecanoate) (abbreviation: P3HB3HD), poly(3-hydroxybutyrate-co-3-hydroxyvalerate-co-3-hydroxyhexanoate) (abbreviation: P3HB3HV3HH), etc. Among them, PHB, P3HB3HH, P3HB3HV, and P3HB4HB are preferred because they are easy to produce industrially. Only one type of P3HB may be used, or two or more types may be used in combination.

[0035] The resin layer preferably contains P3HB in an amount of 50% by weight or more, more preferably 70% by weight or more, even more preferably 80% by weight or more, and even more preferably 90% by weight or more. By using P3HB as a main component, the resin layer can exhibit biodegradability.

[0036] Among P3HB, P3HB3HH is particularly preferred from the viewpoints that by changing the composition ratio of the repeating units, it is possible to change the melting point and crystallinity, thereby adjusting physical properties such as Young's modulus and heat resistance, and that it is possible to impart physical properties between those of polypropylene and polyethylene. It is also easy to produce industrially and is a physically useful plastic.

[0037] The resin layer preferably contains P3HB3HH in an amount of 50% by weight or more, more preferably 70% by weight or more, even more preferably 80% by weight or more, and even more preferably 90% by weight or more. By using P3HB3HH as a main component, the resin layer can exhibit biodegradability, particularly seawater degradability.

[0038] The average content ratio of each constituent monomer in P3HB is preferably 3HB unit / other hydroxyalkanoate unit=97-70 / 3-30 (mol% / mol%), and more preferably 3HB unit / other hydroxyalkanoate unit=94-82 / 6-18 (mol% / mol%). When the average content ratio of other hydroxyalkanoate units in P3HB is 3 mol% or more, good adhesion can be obtained by heat sealing using the resin layer. In addition, P3HB having an average content ratio of other hydroxyalkanoate units of 30 mol% or less does not have an excessively slow crystallization rate and is relatively easy to manufacture.

[0039] When P3HB is P3HB3HH, P3HB3HH having an average content of 3HH of 3 to 30 mol % in the total of 3HB and 3HH may be composed of one type of P3HB3HH, or may be composed of a mixture of at least two types of P3HB3HH having different content ratios of constituent monomers, or may be composed of a mixture of at least one type of P3HB3HH and PHB.

[0040] A combination of P3HB3HH or PHB in the mixture is preferably a combination of P3HB3HH having a 3HH unit content of 8 to 25 mol% in the total of 3HB and 3HH and P3HB3HH or PHB having a 3HH unit content of less than 8 mol% in the total of 3HB and 3HH. By using such a combination, during the formation of a resin layer by heat drying or heat sealing as described below, the fluidity of the resin layer is ensured by P3HB3HH having a content of HH units as a low melting point component of 8 to 25 mol% in the total of 3HB and 3HH, while the crystals of P3HB3HH or PHB having a 3HH unit content of less than 8 mol% are not completely melted but act as crystal nuclei, thereby accelerating the crystal solidification of the resin layer after heat melting, which is suitable for improving the productivity of the laminate and the molded article obtained by heat sealing the laminate.

[0041] In the above combination, the content of 3HH units in P3HB3HH, which has a content of 3HH units of less than 8 mol% in the total of 3HB and 3HH, is preferably 5 mol% or less, more preferably 3 mol% or less, and even more preferably 1 mol% or less. The lower limit of the content of 3HH units in P3HB3HH is not particularly limited, but may be, for example, 0.1 mol% or more.

[0042] The amount of P3HB3HH or PHB having a 3HH unit content of less than 8 mol% is not particularly limited, but is preferably 0 to 50% by weight based on the total P3HB resin contained in the resin layer. When it is used, it is preferably 1 to 50% by weight, more preferably 3 to 30% by weight, even more preferably 4 to 20% by weight, and particularly preferably 5 to 15% by weight.

[0043] The average content ratio of each constituent monomer in P3HB can be determined by a method known to those skilled in the art, for example, the method described in paragraph

[0047] of WO 2013 / 147139 or by NMR measurement. The average content ratio means the molar ratio of 3HB and 3HH in the entire PHBH contained in the resin layer, and means the molar ratio of each monomer contained in the entire mixture when P3HB3HH is a mixture containing at least two types of P3HB3HH or a mixture containing at least one type of P3HB3HH and PHB.

[0044] The weight average molecular weight (hereinafter sometimes referred to as Mw) of the PHA contained in the resin layer can be appropriately selected, but from the viewpoint of achieving both mechanical properties and processability, it is preferably 100,000 to 900,000, more preferably 150,000 to 850,000, and even more preferably 200,000 to 800,000. When the weight average molecular weight of P3HB is 100,000 or more, the mechanical properties are good, and when it is 900,000 or less, good adhesion can be obtained by heat sealing.

[0045] The weight average molecular weight of the PHA can be determined as the polystyrene-equivalent molecular weight by gel permeation chromatography (GPC) (Shodex GPC-101 manufactured by Showa Denko K.K.) using a polystyrene gel (Shodex K-804 manufactured by Showa Denko K.K.) in a column and chloroform as the mobile phase.

[0046] A specific method for producing P3HB3HH is described in, for example, International Publication No. 2010 / 013483. Commercially available products of P3HB3HH include Kaneka Biodegradable Polymer Green Planet (registered trademark) manufactured by Kaneka Corporation.

[0047] The resin layer may contain, to the extent that the effects of the invention are not impaired, one or more of the following: resins other than PHA, adhesives, dispersants or emulsifiers, pH adjusters, inorganic fillers, colorants such as pigments and dyes, odor absorbers such as activated carbon and zeolite, fragrances such as vanillin and dextrin, plasticizers, antioxidants, weather resistance improvers, ultraviolet absorbers, crystal nucleating agents, lubricants, release agents, water repellents, antibacterial agents, sliding property improvers, etc. However, these are optional components, and the resin layer may not contain these components.

[0048] The resin other than PHA that can be used in the resin layer is not particularly limited, but is preferably a biodegradable resin.Specific examples include aliphatic polyester resins such as polycaprolactone, polybutylene succinate adipate, polybutylene succinate, and polylactic acid, and aliphatic aromatic polyester resins such as polybutylene adipate terephthalate and polybutylene azelate terephthalate.The amount of these resins other than PHA may be 50 parts by weight or less, 30 parts by weight or less, or 10 parts by weight or less relative to 100 parts by weight of PHA.In addition, it may be 5 parts by weight or less, or 1 part by weight or less.

[0049] [Method for producing laminate] A method for producing a laminate according to one aspect of this embodiment sequentially comprises the steps of: applying an aqueous coating liquid containing an acrylic resin to at least one surface of a paper substrate (A), followed by heating to form a primer layer (B) (step (i)); and applying an aqueous dispersion containing a poly(hydroxyalkanoate) resin to the surface of the primer layer (B) to form a coating film, heating the coating film so that the surface temperature is within the melting point (Tm) of the poly(hydroxyalkanoate) resin + 5°C to Tm + 20°C to form a resin layer (C) (step (ii)). The above-mentioned production method makes it easy to obtain a laminate having excellent interlayer adhesion strength between the primer layer and the paper base material, and between the primer layer and the resin layer, while suppressing pinholes in the resin layer. The primer layer (B) and the resin layer (C) may be formed by repeatedly applying an aqueous acrylic resin coating liquid or an aqueous PHA resin dispersion, heating, drying, and forming a film, for each of them. The aqueous acrylic resin coating liquid or the aqueous PHA resin dispersion used in the repeated operation may be one type of material repeatedly used, or a combination of multiple types of materials may be used. The method of applying the aqueous acrylic resin coating liquid and the aqueous PHA resin dispersion liquid is not particularly limited, and known methods can be used appropriately.Specifically, spraying method, scattering method, slit coater method, air knife coater method, roll coater method, bar coater method, comma coater method, blade coater method, screen printing method, gravure printing method, etc. can be used.Before applying the aqueous acrylic resin coating liquid, a process of performing surface treatment such as corona treatment, plasma treatment, and flame treatment on the paper substrate may be performed. It is preferable that the heat treatment for forming the primer layer and the resin layer is carried out so that the temperature that the laminate actually reaches is less than 100° C. for the primer layer, and equal to or higher than the melting point of the PHA resin for the subsequent resin layer. By controlling the temperature at this level, the decrease in moisture content due to excessive drying of the paper base material is suppressed, and problems such as a decrease in mechanical strength of the laminate and breakage can be avoided. In the heat treatment for forming the resin layer, pinholes can be suppressed by heating so that the surface temperature of the coating film formed by coating an aqueous dispersion of the poly(hydroxyalkanoate) resin becomes the melting point (Tm) of the poly(hydroxyalkanoate) resin + 5°C to Tm + 20°C. The lower limit of the surface temperature of the coating film is preferably Tm + 7°C, and more preferably Tm + 10°C, and the upper limit is preferably Tm + 18°C, and more preferably Tm + 15°C. The melting point of the poly(hydroxyalkanoate) resin refers to the peak top temperature in the crystal melting curve in the differential scanning calorimetry. When multiple peaks exist, it refers to the peak top temperature on the highest temperature side. The temperature reached by the laminate during heating can be confirmed by measuring with an irreversible temperature indicator, a thermocouple, a non-contact laser thermometer, or the like. The laminate obtained by sequentially carrying out the above steps (i) and (ii) is preferably further subjected to heat treatment at a temperature below the melting point of the PHA resin, and the heat-retention temperature is preferably 35 to 70° C., more preferably 40 to 60° C. By keeping the temperature at this temperature, the crystallization of the PHA resin after the heat treatment is accelerated, which is suitable for improving the productivity of the laminate. In particular, it is possible to reduce blocking caused by adhesion between the base layer and the resin layer, which occurs when the laminate is continuously produced and wound into a roll, as described below. This heat retention treatment can be carried out using the same heating method as the heat treatment described above, such as hot air heating, infrared heating, microwave heating, roll heating, hot plate heating, etc., which can be used alone or in combination of two or more types. The heat-retaining temperature in the heat-retaining treatment does not refer to the actual temperature of the laminate, but refers to the set temperature of the equipment, such as a drying furnace or rolls, used in the heat-retaining treatment. The treatment time in the heat-retaining treatment can be appropriately set in consideration of the effect of the heat-retaining treatment, and is preferably, for example, 3 seconds to 1 minute, more preferably 5 to 30 seconds, and even more preferably 10 to 20 seconds. (Formation of primer layer) The solid content of the aqueous coating liquid containing the acrylic resin used to form the primer layer is not particularly limited, but is preferably 30% by weight or more, more preferably 40% by weight or more, in order to keep the amount of heat required for drying low. The upper limit of the solid content is preferably 60% by weight or less, and if it exceeds 60% by weight, the viscosity of the aqueous coating liquid becomes too high, which tends to impair the uniformity of the thickness of the coating film. In the laminate according to this embodiment, the coating amount (dry weight) of the primer layer (B) may be appropriately selected depending on the type of paper base material so as to fill the unevenness of the pulp. 2 More than 5.0g / m 2 The weight is preferably less than 1.0 g / m 2 If it is less than 5.0 g / m, the filling of the paper base material may be insufficient. 2 If the amount exceeds this range, not only will it be uneconomical because material costs will increase and a large amount of heat will be required for heating to dry and form the film, which will increase the load on the equipment, but the biodegradability of the laminate will tend to be hindered. The weight per unit area is 1.5 g / m 2 More than 4.5g / m 2 More preferably, it is 2.0 g / m or less. 2 More than 3.0g / m 2 The following are particularly preferred: (Formation of resin layer) As a method for forming the resin layer according to the present embodiment, it is preferable to use a method of applying (coating) an aqueous dispersion in which resin particles containing at least PHA are dispersed in water, and then heating and drying to form the resin layer (hereinafter, sometimes referred to as a "coating method"). By using the aqueous dispersion, after forming a primer layer containing the acrylic resin, the aqueous dispersion containing PHA can be continuously applied to the primer layer to form a resin layer, so that it is possible to manufacture a laminate with high productivity. The aqueous dispersion can be prepared, for example, by referring to International Publication No. 2021 / 059592.

[0050] The solids concentration of the PHA in the aqueous dispersion may be appropriately set, for example, 25 to 65% by weight, preferably 30 to 55% by weight, and more preferably 35 to 50% by weight. When the solids concentration of the PHA in the aqueous dispersion is within the above range, the viscosity of the solution is not too high, so that uniform application is possible, and the necessary thickness of the coating film can be maintained, thereby making it possible to suppress defects in the coating film.

[0051] The average particle size of the PHA particles in the aqueous dispersion may be, for example, 0.1 to 50 μm, preferably 0.5 to 30 μm, and more preferably 0.8 to 20 μm, from the viewpoint of achieving both PHA productivity and uniformity during application. When the average particle size is 0.1 μm or more, PHA can be easily obtained by either microbial production or chemical synthesis. When the average particle size is 50 μm or less, the occurrence of coating unevenness can be avoided. The average particle size of the PHA particles in the aqueous dispersion can be calculated by adjusting the aqueous dispersion containing PHA to a predetermined concentration using a general-purpose particle sizer such as a Microtrack particle sizer (manufactured by Nikkiso, FRA), and calculating the particle size corresponding to 50% accumulation of all particles in a normal distribution.

[0052] The aqueous dispersion may not contain a dispersant, but it is preferable to contain a dispersant to stabilize the dispersion. Examples of dispersants include anionic surfactants such as sodium lauryl sulfate and sodium oleate, cationic surfactants such as lauryl trimethylammonium chloride, nonionic surfactants such as glycerin fatty acid esters and sorbitan fatty acid esters, polyvinyl alcohol derivatives such as polyvinyl alcohol, carboxy-modified polyvinyl alcohol, sulfonated polyvinyl alcohol, and ethylene-modified polyvinyl alcohol, cellulose derivatives such as methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose, starch derivatives such as starch, oxidized starch, and etherified starch, and water-soluble polymers such as chitin, chitosan, casein, and gum arabic. These may be used alone or in combination of two or more. Among them, methyl cellulose and polyvinyl alcohol are preferable because they can be easily used to prepare an aqueous solution when added to the dispersion industrially.

[0053] The amount of dispersant added is not particularly limited, but is preferably 0.2 to 10% by weight based on the solid content of the PHA. When the amount of dispersant added is 0.2% by weight or more, the stabilizing effect of the dispersant tends to be easily obtained, and when it is 10% by weight or less, deterioration of physical properties and coloring due to the inclusion of an excess emulsifier in the PHA can be avoided.

[0054] The coating amount of the resin layer is not particularly limited and can be appropriately determined in consideration of the performance and productivity required for the resin layer. Specifically, the coating amount is 1.0 g / m2 in terms of dry weight. 2 More than 80g / m 2 Preferably, the thickness is 5.0 g / m or less. 2 More than 40g / m 2 Less than 10 g / m is more preferable. 2 More than 30g / m 2 When the coating amount of PHA is within the above range, the resin layer can have a strength sufficient for use, and functions such as water resistance, oil resistance, and heat sealability can be efficiently exhibited. 2 If the melting temperature exceeds this range, the resin will not melt sufficiently, making it difficult to form a uniform resin layer.

[0055] The thickness of the resin layer (thickness after drying) correlates with the coating amount of the PHA, and may be, for example, 0.5 to 70 μm, or 5 to 30 μm.

[0056] It is also preferable to set the coating weight of the PHA and the basis weight of the substrate so that the value obtained by dividing the coating weight (dry weight) of the PHA by the basis weight of the above-mentioned paper substrate (coating weight / basis weight of substrate) is 0.05 to 0.45. Within this range, a laminate can be obtained that has a good balance between curl suppression and water resistance and oil resistance due to the resin layer, and the laminate can be efficiently produced by the production method according to the present disclosure. (Other processes) The obtained laminate may be subjected to a heating treatment and an optional heat retention treatment, and then water may be applied to the paper substrate, so-called moisture conditioning treatment, to adjust the moisture content of the paper substrate, if necessary. A flattening treatment using a machine calendar or a soft calendar may also be performed. The method of applying water to the paper substrate is not particularly limited as long as it can be applied uniformly to the paper substrate. For example, known methods such as spraying, scattering, slit coater, air knife coater, roll coater, bar coater, comma coater, blade coater, screen printing, and gravure printing can be used alone or in combination. Among them, the spraying method is preferred because it can be applied uniformly without unevenness with a small amount of water. The spraying of water can be carried out, for example, using a commercially available liquid application device characterized by non-contact application. The water may contain additives such as moisturizers, such as glycerin and propylene glycol, various fragrances, and preservatives, as long as the purpose of the water is not impaired. The temperature of the water to be sprayed is not particularly limited, but is preferably 50°C or lower, more preferably 30°C or lower. This temperature can promote the crystallization and solidification of the PHA-based resin in addition to the moisture control of the paper, and is suitable for suppressing blocking caused by adhesion between the base layer and the resin layer, which occurs when the laminate is continuously produced and wound into a roll, as described below. The lower limit temperature of the water is not particularly limited, but is preferably 5°C or higher, more preferably 10°C or higher, from the viewpoint of preventing condensation. In particular, it is preferable to use a cooling medium at room temperature (about 10 to 30°C) that has not been temperature-controlled. The amount of water to be sprayed may be appropriately determined in consideration of the moisture content of the substrate after the drying step and the moisture content of the target substrate. The moisture content of the target substrate is not particularly limited, but may be, for example, about 5 to 8%, or may be 6 to 7%. The series of steps involved in forming the laminate may be carried out on a paper base material that has been cut into a plate shape in advance, or may be carried out continuously by preparing a paper base material wound into a roll as a raw material and continuously unwinding and transporting it using a conventional transport device.

[0057] (Second resin layer) In another aspect of the laminate of the present embodiment, a second resin layer may be further laminated on the resin layer. In this aspect, the paper base material, the resin layer, and the second resin layer are laminated in this order.

[0058] In this embodiment, the resin layer functions as an anchor coat layer between the substrate and the second resin layer. Also, by providing the second resin layer, it is possible to impart a high level of water resistance and oil resistance to the laminate. In this embodiment, the resin layer only needs to have adhesive properties between the paper base material and the second resin layer. When the second resin layer is formed, the thickness (dry thickness) of the resin layer may be 0.5 to 100 μm, preferably 0.7 to 15 μm, and more preferably 1 to 10 μm. The second resin layer may be the outermost layer in the laminate, or another layer may be laminated on the second resin layer.

[0059] The second resin layer preferably contains a biodegradable resin and exhibits biodegradability. This can increase the biodegradability of the entire laminate. Usable biodegradable resins include the resins described above for the resin layer, specifically, PHA, aliphatic polyester resins, aliphatic aromatic polyester resins, and the like. The second resin layer may also contain additives that are usually added to resin materials, as long as they do not impair the effects of the invention.

[0060] The thickness (dry thickness) of the second resin layer is not particularly limited and can be appropriately determined in consideration of the performance and productivity required of the second resin layer, and may be, for example, about 5 to 100 μm.

[0061] The method for forming the second resin layer on the resin layer is not particularly limited, and examples thereof include a coating method, an extrusion lamination method, and a thermal lamination method. (Printing layer) In the laminate according to the present embodiment, the printed layer is an optional layer. When the laminate has a printed layer, the printed layer is preferably formed on the surface opposite to the resin layer.

[0062] The details of the printing layer are not particularly limited, and the printing layer can be formed by a known printing method using a known printing ink. Examples of the printing method include gravure printing, offset printing, gravure offset printing, flexographic printing, and inkjet printing. The printing ink may be either solvent-based or water-based. The printing layer may be a single layer or may be composed of multiple layers.

[0063] A protective layer for protecting the printed layer may be formed on the printed layer. The protective layer may be selected from known materials, for example, a solvent-based or water-based lacquer containing a resin or an additive.

[0064] [Molded body] The laminate that can be produced by this embodiment can be formed into a molded body (hereinafter, also referred to as the "present molded body") by shaping a laminate of a predetermined shape. The molded body includes the laminate and has a desired size and shape. The present molded body is formed from a laminate including a resin layer containing PHA, and is therefore advantageous in various applications.

[0065] In one embodiment of the present disclosure, the present molded article may be the present laminate itself, or may be a product obtained by subjecting the present laminate to secondary processing. From the viewpoint of marine pollution countermeasures, the present molded product is preferably used as various packaging materials, for example, wrapping paper, various bags, lid materials, cups, trays and other containers, and can be suitably used in the fields of food, cosmetics, electronics, medicine, pharmaceuticals, etc. In particular, since the present laminate has excellent oil resistance and the PHA of the resin layer has good heat resistance, it is preferable as wrapping paper, bags and containers used for instant noodles, instant soup, coffee, prepared foods, boxed lunches and microwaveable foods. The secondary processing can be carried out by any method known in the art, for example, by using various bag making machines, filling and packaging machines, etc. Processing can also be carried out by using devices such as paper tray press molding machines, paper cup molding machines, punching machines, and box making machines. In these processing machines, known techniques can be used for bonding the molded body, and in addition to the usual heat sealing method, for example, the impulse sealing method, ultrasonic sealing method, high frequency sealing method, hot air sealing method, frame sealing method, etc. can be used. The heat sealing may be carried out between the paper base layer and the resin layer, or between the resin layers.

[0066] The heat-sealing temperature when heat-sealing the resin layers of the laminate is usually 150 to 200° C., preferably 160 to 190° C., and more preferably 170 to 180° C., when both sides are heated using a heat-sealing tester with a seal bar. The heat-sealing temperature when heat-sealing the resin layer and the paper base layer of the laminate is usually 160 to 220° C., preferably 170 to 210° C., and more preferably 180 to 200° C., when both sides are heated using a heat-sealing tester with a seal bar. When the temperature is within the above range, melting of the resin near the sealed portion can be avoided, and an appropriate resin layer thickness and seal strength can be ensured.

[0067] The heat sealing pressure when heat sealing the laminate varies depending on the adhesion method. When a heat-sealing tester having a seal bar is used, the heat sealing pressure of the molded body is usually 0.1 MPa or more, preferably 0.3 MPa or more. If the pressure is more than the above value, sufficient adhesive strength by heat sealing can be ensured.

[0068] In order to improve the physical properties of the molded article according to this embodiment, it is also possible to compound the molded article with another molded article (e.g., fiber, thread, rope, woven fabric, knitted fabric, nonwoven fabric, paper, film, sheet, tube, plate, rod, container, bag, part, foam, etc.) made of a material different from the molded article. These materials are also preferably biodegradable.

[0069] The following items enumerate preferred aspects of the present disclosure, but the present invention is not limited to the following items. [Item 1] A method for producing a laminate having a paper base material (A) and, on at least one side of the paper base material (A), a primer layer (B) and a resin layer (C) containing a poly(hydroxyalkanoate)-based resin, the method comprising sequentially carrying out at least the following steps (i) and (ii): Process (i); A step of applying an aqueous coating liquid containing an acrylic resin to the surface of the paper substrate (A) and then heating the applied liquid to form a primer layer (B). Step (ii); A process of forming a coating film by applying an aqueous dispersion containing a poly(hydroxyalkanoate) resin to the surface of the primer layer (B) obtained in the process (i), and heating the surface of the coating film to a temperature of melting point (Tm) of the poly(hydroxyalkanoate) resin + 5°C to Tm + 20°C to form a resin layer (C). [Item 2] 2. The method according to item 1, wherein the coating amount (dry weight) per unit area of ​​the resin layer (C) divided by the basis weight of the paper base material (A) (coating amount / basis weight of base material) is 0.05 to 0.45. [Item 3] The coating amount (dry weight) of the resin layer (C) per unit area is 1 g / m 2 More than 80g / m 2 3. The method according to item 1 or 2, wherein: [Item 4] The paper base material (A) has a basis weight of 40 g / m 2 More than 400g / m 2 The method for producing a semiconductor device according to any one of Items 1 to 3, wherein the semiconductor device is a semiconductor device having a structure as described below. [Item 5] 5. The method according to any one of items 1 to 4, wherein the poly(hydroxyalkanoate)-based resin is a poly(3-hydroxybutyrate)-based resin. [Item 6] 6. The method according to item 5, wherein the poly(3-hydroxybutyrate)-based resin is a copolymer containing 3-hydroxybutyrate units and other hydroxyalkanoate units. [Item 7] Item 7. The method according to item 6, wherein the poly(3-hydroxybutyrate)-based resin contains a poly(3-hydroxybutyrate)-based resin having a content of 3-hydroxybutyrate units of 70 to 97 mol% in the total of 3-hydroxybutyrate units and other hydroxyalkanoate units. [Claim 8] 7. The method according to item 6, wherein the other hydroxyalkanoate units include 3-hydroxyhexanoate units. [Item 9] 9. A method for producing a molded body, comprising: producing a laminate by the production method according to any one of items 1 to 8; and shaping the laminate. [Item 10] Item 10. The method according to item 9, wherein the molded article is a packaging bag, a lid, or a container. EXAMPLES

[0070] The present invention will be specifically described below with reference to examples, but the technical scope of the present invention is not limited to these examples.

[0071] [Production Example 1] The culture was performed according to the method described in the examples of WO 2015 / 146195, and the weight-average molecular weight was adjusted and purified according to the method described in WO 2004 / 041936. The P3HB3HH composition (average ratio in P3HB3HH = 89.5 mol% / 10.5 mol%, PHB content in the composition is 6.3 wt%) containing P3HB3HH and PHB and having a weight-average molecular weight of 220,000 was obtained as an aqueous suspension containing 50 wt% of the solid content. The melting point of the P3HB3HH composition was measured by filling 2 to 5 mg of the dried product obtained by drying the aqueous suspension in a hot air dryer at 60 ° C. into an aluminum pan, and heating the dried product at a rate of 10 ° C. / min from 20 ° C. to 190 ° C. under a nitrogen stream using a differential scanning calorimeter. The P3HB3HH composition had two melting point peaks at 110° C. and 160° C., and the melting point of P3HB3HH was determined to be the highest peak temperature, 160° C. Partially saponified polyvinyl alcohol (Kuraray Co., Ltd., Kuraray Poval: 5-88) as a dispersant was added together with water so that the amount was 3 parts by weight per 100 parts by weight of the resin contained in the aqueous suspension, and the mixture was stirred to obtain aqueous dispersion HB-1 containing P3HB3HH, PHB, and the dispersant at a solids concentration of 40% by weight. [Production Example 2] In the same manner as in Production Example 1, an aqueous suspension containing 50% by weight of a P3HB3HH composition containing P3HB3HH and PHB and having a weight-average molecular weight of 550,000 (average ratio 3HB / 3HH in P3HB3HH = 89.5 mol% / 10.5 mol%, the content of PHB in the composition is 6.3% by weight) was prepared in a solid content concentration of 50% by weight, and the melting point was measured. The P3HB3HH composition had two melting point peaks at 110 ° C. and 160 ° C., and the melting point of P3HB3HH was determined to be the highest peak temperature of 160 ° C. Methylcellulose (manufactured by Shin-Etsu Chemical Co., Ltd., Metolose: SM-15) was added as a dispersant together with water so that the amount was 0.3 parts by weight relative to 100 parts by weight of the resin contained in the aqueous suspension, and the mixture was stirred to obtain an aqueous dispersion HB-2 containing 40% by weight of solid content of P3HB3HH, PHB, and the dispersant in total. [Production Example 3] The aqueous suspension obtained in Production Example 2 was used, and partially saponified polyvinyl alcohol (Kuraray Co., Ltd., Kuraray Poval: 5-88) was added as a dispersant together with water so that the amount was 3 parts by weight per 100 parts by weight of the resin contained in the aqueous suspension, and the mixture was stirred to obtain aqueous dispersion HB-3, which contained 40% by weight of solids in total, including P3HB3HH, PHB, and the dispersant. (Primer layer and resin coating weight (dry weight)) Each coated paper was cut into a 100 mm square and its weight was measured. The weight of the base paper was subtracted from this weight value, and the result was multiplied by 100 to obtain the weight per unit area of ​​the resin content.

[0072] Example 1 Basis weight 50g / m 2 Bleached kraft paper, dry weight 1.5g / m 2 A water-based acrylic resin coating solution AC-1 [SEIKOAT (registered trademark) RE-2273, manufactured by Seiko PMC Corporation, solid content concentration 40% by weight, glass transition temperature (Tg) -11°C] was applied using a bar coater so that the surface was coated with a primer layer. The primer layer was then heated for 2 minutes in a hot air drying oven set at 100°C. The irreversible temperature indicator (3E-80 manufactured by NOF Corp.) attached to the paper (coated surface) indicated 90°C. Next, a 20 g / m2 dry weight acrylic resin coating solution was applied to the paper. 2 After applying the aqueous dispersion HB-1 using a bar coater so that the surface temperature became 180°C, the laminate was heated for 2 minutes in a hot air drying oven set at 180°C to form a resin layer, thereby obtaining a laminate. The irreversible temperature indicator (5E-170 manufactured by NOF Corp.) attached to the upper end of the primer layer showed 170°C (corresponding to the surface temperature of the coating film).

[0073] Example 2 Water-based acrylic resin coating liquid dry weight 2.0g / m 2 A laminate was obtained in the same manner as in Example 1, except for the above.

[0074] Example 3 Basis weight 220g / m 2 A laminate was obtained in the same manner as in Example 1, except that the cup base paper was used and HB-2 was used as the aqueous dispersion.

[0075] Example 4 The dry weight of the water-based acrylic resin coating liquid is 2.0 g / m 2 A laminate was obtained in the same manner as in Example 3, except for the above. Example 5 A laminate was obtained in the same manner as in Example 3, except that the aqueous dispersion was changed to HB-3.

[0076] Comparative Example 1 Basis weight 50g / m 2 of bleached kraft paper on one side, dry weight 20 g / m 2 After applying the aqueous dispersion HB-1 using a bar coater so that the paper was heated for 2 minutes in a hot air drying oven set at 180°C to form a resin layer, and a laminate was obtained. The irreversible temperature indicator (5E-170, manufactured by NOF Corp.) attached to the upper end of the paper indicated 170°C.

[0077] Comparative Example 2 Basis weight 220g / m 2 A laminate was obtained in the same manner as in Comparative Example 1, except that the cup base paper was used and HB-2 was used as the aqueous coating liquid.

[0078] Comparative Example 3 A laminate was obtained in the same manner as in Comparative Example 1, except that the resin layer was formed by heating for 2 minutes in a hot air drying oven set at 210° C. The irreversible temperature indicator (5E-170 manufactured by NOF Corp.) attached to the paper (coated surface) indicated 200° C. Comparative Example 4 A laminate was obtained in the same manner as in Example 1, except that the resin layer was formed by heating for 2 minutes in a hot air drying oven set at 170° C. The irreversible temperature indicator (3E-150 manufactured by NOF Corp.) attached to the upper end of the primer layer showed a temperature of 160° C. Comparative Example 5 A laminate was obtained in the same manner as in Example 1, except that the resin layer was formed by heating for 2 minutes in a hot air drying oven set at 210° C. The irreversible temperature indicator (5E-170 manufactured by NOF Corp.) attached to the upper end of the primer layer showed 200° C.

[0079] The laminates obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were evaluated for oil resistance, curl height, and adhesion between the paper base material and the resin layer by the methods described below. The results are shown in Table 1. [Oil resistance] The laminate obtained in each Example or Comparative Example was cut into a 100 mm square, and Ageless Seal Check test liquid (manufactured by Mitsubishi Gas Chemicals) was sprayed onto the resin layer side, and wiped off after 60 seconds. It was visually confirmed whether the test liquid had soaked in, and the evaluation was performed based on the following criteria. <Evaluation criteria> ◎: The number of spot-like stains with a diameter of 2 mm or more was 0 to 3. ○: The number of spot-like stains with a diameter of 2 mm or more was 4 to 9. ×: There were 10 or more spot-like stains having a diameter of 2 mm or more.

[0080] [Curling] A test piece measuring 300 mm in the machine direction and 200 mm in the width direction was cut out from each laminate obtained in each Example or Comparative Example. When the test piece was placed on a flat surface with the resin layer facing up, the maximum height of the end of the test piece from the surface on which it was placed was taken as the curl height, and evaluation was performed based on the following criteria. <Evaluation criteria> ○: Curl height is less than 5 mm ×: Curl height is 5mm or more [Adhesion between paper base material (A) and resin layer (C)] A 30 mm long cross cut was made with a cutter knife in the resin layer of the laminate obtained in each Example and Comparative Example, and cellophane tape (registered trademark, model number: Nichiban, CT-18) was attached to the point where the cuts intersected. The degree of peeling when peeled off by hand was evaluated based on the following criteria. <Evaluation criteria> ○: The resin layer does not peel off at all, or the paper layer is destroyed. △: Some damage to the paper layer occurs, but peeling of the resin layer occurs in most areas ×: Resin layer peels off, but paper layer does not break

[0081] [Table 1]

[0082] From Table 1, it can be seen that in Examples 1 to 5, in which a primer layer was formed using an aqueous acrylic resin coating liquid and a poly(hydroxyalkanoate) resin layer was formed on the surface of the primer layer under the heating conditions of the present invention, penetration of the test liquid into the resin layer surface was reduced, oil resistance was good, and the adhesion strength between the paper and the resin layer was excellent, compared to Comparative Examples 1 to 3, in which a resin layer was formed without forming a primer layer.

[0083] In Comparative Example 3, the primer layer was not formed, and the coating film was heated to a higher surface temperature in an attempt to promote melting of the resin component (particles). Although the adhesion strength between the paper layer and the resin layer was improved, the penetration of the test liquid was not reduced, and the curling property of the obtained laminate deteriorated. In Comparative Example 4, the primer layer was formed, and a poly(hydroxyalkanoate)-based resin layer was formed on the surface of the primer layer. However, the heat treatment temperature when forming the resin layer was low, and the resin was not sufficiently fused, resulting in insufficient oil resistance and adhesion strength between the paper layer and the resin layer. On the other hand, in Comparative Example 5, the heat treatment temperature when forming the oil-resistant poly(hydroxyalkanoate)-based resin layer was too high, and the curling property of the laminate also deteriorated.

Claims

1. A method for producing a laminate having a paper base material (A) and, on at least one side of the paper base material (A), a primer layer (B) and a resin layer (C) containing a poly(hydroxyalkanoate)-based resin, the method comprising sequentially carrying out at least the following steps (i) and (ii): Step (i); A step of applying an aqueous coating liquid containing an acrylic resin to the surface of the paper substrate (A) and then heating the applied liquid to form a primer layer (B). Step (ii); A process for forming a coating film by applying an aqueous dispersion containing a poly(hydroxyalkanoate) resin to the surface of the primer layer (B) obtained in the process (i), and heating the coating film so that the surface temperature of the coating film becomes the melting point (Tm) of the poly(hydroxyalkanoate) resin + 5°C to Tm + 20°C, thereby forming a resin layer (C).

2. The manufacturing method according to claim 1, wherein the value obtained by dividing the coating amount (dry weight) per unit area of ​​the resin layer (C) by the basis weight of the paper base material (A) (coating amount / basis weight of base material) is 0.05 to 0.

45.

3. The coating amount (dry weight) of the resin layer (C) per unit area is 1 g / m 2 80g / m or more 2 The method according to claim 1 or 2, wherein:

4. The paper base material (A) has a basis weight of 40 g / m 2 More than 400g / m 2 The method according to claim 1 or 2, wherein:

5. The method according to claim 1 or 2, wherein the poly(hydroxyalkanoate)-based resin is a poly(3-hydroxybutyrate)-based resin.

6. The method according to claim 5, wherein the poly(3-hydroxybutyrate)-based resin is a copolymer containing 3-hydroxybutyrate units and other hydroxyalkanoate units.

7. The method according to claim 6, wherein the poly(3-hydroxybutyrate)-based resin contains a poly(3-hydroxybutyrate)-based resin in which the content of 3-hydroxybutyrate units in the total of 3-hydroxybutyrate units and other hydroxyalkanoate units is 70 to 97 mol %.

8. The method according to claim 6, wherein the other hydroxyalkanoate units include 3-hydroxyhexanoate units.

9. A method for producing a molded body, comprising: a step of producing a laminate by the production method according to claim 1 or 2; and a step of shaping the laminate.

10. The method according to claim 9 , wherein the molded article is a packaging bag, a lid, or a container.

Citation Information

Patent Citations

  • Aqueous dispersion liquid and use of same

    WO2021075412A1